Flumioxazin effects on soybean canopy formation and soil-borne pathogen presence. (21st October 2020) - Priess, Grant L; Norsworthy, Jason K; Roberts, Trenton L; Spurlock, Terry N
Abstract: Rapid crop canopy formation is important to reduce weed emergence and selection for herbicide resistance. Field experiments were conducted in 2017 and 2018 in Fayetteville, AR, to evaluate the impacts of PRE applications of flumioxazin on soybean injury, soybean density, canopy formation, and incidence of soil-borne pathogens. Flumioxazin was applied at 0, 70, and 105 g ai ha −1 to predetermined flumioxazin-tolerant and -sensitive soybean varieties. Flumioxazin at 70 g ha −1 injured the tolerant and sensitive varieties from 0% to 4% and 14% to 15%, respectively. When averaged over flumioxazin rates, density of the sensitive variety was only reduced in 2017 when activation of flumioxazin was delayed 7 d. Compared to the tolerant soybean variety, flumioxazin at 70 g ha −1 delayed the sensitive variety from reaching 20%, 40%, 60%, and 80% groundcover by 15, 16, 11, and 5 d, respectively. No delay in canopy closure (95% groundcover) was observed with either variety. Consequently, no yield loss occurred for either variety following a flumioxazin application. Flumioxazin did not impact root colonization of Didymella, Fusarium, Macrophomina, or Rhizoctonia . Pythium colonization of the soybean stem was increased by flumioxazin in 2017, but not in 2018. Increased injury, delays in percent groundcover, and an increase in Pythium colonization of soybean following a flumioxazin application may warrant the need for other soil-applied herbicides at soybean planting. Alternatively, soybean injury and delays in percent groundcover following flumioxazin applications can be mitigated through appropriate variety selection; however, comprehensive screening is needed to determine which varieties are most tolerant to flumioxazin.